Building enterprise surrouding and its quantitative evaluation - Ginevičius, R. (Journal of Civil Engineering and Management, 1995)
The situation of any enterprise depends on several various factors. From the wholeness the organization theory defines and analyses only the essential ones. One of them is the surrounding, which can be described by three dimensions which reflect its completeness, dynamics and the dependence of the organization on it. The first one evaluates the exterior factors, which are necessary to be reconsidered while taking decisions, the number; the differences between these factors, and also their distribution among seperate surrounding regulations. The second one evaluates the organizational important surrounding factors’ frequency of changes, intensity and regularity. The third is—the number of partners providing the production supply and also their degree of interrelation. Evaluating all these dimensions quantitively, it is necessary to pay attention to the specific of building production. Article in Lithuanian. Statybos įmonės aplinka ir jos kiekybinis įvertinimas First Published Online: 26 Jul 2012